Dampak Leverage, Profitabilitas, Likuiditas dan Ukuran Perusahaan Terhadap Kualitas Laba - Fajar Rina Sejati; Entar Sutisman; Dian Pertiwi; Sahrul Ponto; Nurul Hidayah Syamsuddin (Univiversitas Dr. Djar Wattiheluw, 2021)
The purpose of this study was to examine the effects of the leverage, profitability and company size on earnings quality. The sample of this study was using 11 companies in the property, real estate and building contruction sub sector service companies listed on the Indonesian Stock Exchange (IDX) during 2014-2019 period met all the criteria. Empirical evidence suggest that leverange and profitability has no effect on earnings quality. Then, liquidity has negative effect on earnings quality and company size has positiveeffect on earnings quality.